2020
DOI: 10.1016/j.wneu.2020.05.140
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Outpatient Neurosurgical Oncology Care: Lessons Learned for the Future During the COVID-19 Pandemic

Abstract: BACKGROUND: The coronavirus 2019 (COVD-19) pandemic has drastically disrupted the delivery of neurosurgical care, especially for the already at-risk neuro-oncology population. The sudden change to clinic visits has rapidly spurned the implementation of telemedicine. A recommendation care paradigm of neuro-oncologic patients limited by telemedicine has not been reported.-METHODS: A summary of a multi-institution experience detailing the potential benefits, pitfalls, and the necessary considerations to outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 25 publications
0
61
0
1
Order By: Relevance
“…One of the disadvantages that we faced in our study is the inability of some surgeons to perform accurate remote clinical examinations especially motor power assessment in some spinal cases. In the future, we might support modern technologies which would enable us to perform satisfying remote examination [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the disadvantages that we faced in our study is the inability of some surgeons to perform accurate remote clinical examinations especially motor power assessment in some spinal cases. In the future, we might support modern technologies which would enable us to perform satisfying remote examination [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 15 Various eHealth approaches from different medical fields have already been implemented into medical care during the COVID-19 pandemic. [16][17][18] They offer great advantages in terms of patient-professional communication and provide timely symptom management. Rehabilitation programmes which support patients with the SARS-CoV-2 virus in maintaining their physical fitness during individual quarantine have been reported by one centre in Japan.…”
Section: E-mental Health Approachesmentioning
confidence: 99%
“…16 A multi-institutional study investigating potential benefits and pitfalls of telemedicine in outpatient neuro-oncological care during COVID-19 showed that telemedicine is a powerful and possibly preferable tool for the future. 17 Moreover, different clinics in the USA reported a reduction in medical visits per day in primary care practices, due to the use of virtual practices. 18 Furthermore, patients from those clinics had an almost universally positive response to those changes.…”
Section: Introductionmentioning
confidence: 99%
“…Going forward, further application of technologies, for instance digital imaging, remote medication supply, the use of machine learning and artificial intelligence for autonomous robot for examination, and the use of virtual reality environment for training and education purposes are transformational windows of opportunity for safer oncology care and training delivery [40]. Virtual care delivery should be appropriately documented to facilitate billing [41]. National health coverage and commercial medical insurance should reconsider to revise their payment policy and provide reimbursement for telemedicine activities in response to pandemic [42].…”
Section: Impact On Patient Carementioning
confidence: 99%